Comparison of standard and Lewis ECG in detection of atrioventricular dissociation in patients with wide QRS tachycardia. (15th December 2016) - Aksu, Uğur; Kalkan, Kamuran; Gülcü, Oktay; Topcu, Selim; Sevimli, Serdar; Aksakal, Enbiya; Ipek, Emrah; Açıkel, Mahmut; Tanboğa, Ibrahim Halil
Abstract: Background: The atrioventricular (AV) dissociation, which is frequently used in differential diagnosis of wide QRS complex tachycardia (WQCT), is the most specific finding of ventricular tachycardia (VT) with lower sensitivity. Herein, we aimed to show the importance of Lewis lead ECG records to detect 'visible p waves' during WQCT. Method: A total of 21 consecutive patients who underwent electrophysiologic study (EPS) were included in the study. During EPS, by using a quadripolar diagnostic catheter directed to the right ventricular apex, a fixed stimulus was given and the ventriculoatrial (VA) Wenkebach point was found, and a VT was simulated by a RV apical stimulus at 300 ms. The standard and Lewis lead ECG records were taken during this procedure. Result: We detected 'visible p waves' in 7 (33.3%) and 14 (66.7%) patients in the standard and Lewis lead ECG groups, respectively. In terms of the 'visible p waves', there was a statistically significant difference between groups ( p = 0.022). The sensitivity of standard and Lewis lead ECG in determination of the visible p waves was 33.3% and 66.7%, respectively. Conclusion: The Lewis lead ECG can be more informative about AV dissociation than the standard 12 lead ECG. As a result, we could suggest the assessment of the Lewis lead ECG recording in addition to the standard 12 lead ECG in differential diagnosis of VT in patients with WQCT.